Two triphosphate tunnel metalloenzymes from apple exhibit adenylyl cyclase activity - Yuan, Ye; Liu, Zhiguo; Wang, Lili; Wang, Lixin; Chen, Shuangjiang; Niu, Yahong; Zhao, Xin; Liu, Ping; Liu, Mengjun (Frontiers in Plant Science, 2022)
Adenylyl cyclase (AC) is the key catalytic enzyme for the synthesis of 3′,5′-cyclic adenosine monophosphate. Various ACs have been identified in microorganisms and mammals, but studies on plant ACs are still limited. No AC in woody plants has been reported until now. Based on the information on HpAC1, three enzymes were screened out from the woody fruit tree apple, and two of them (MdTTM1 and MdTTM2) were verified and confirmed to display AC activity. Interestingly, in the apple genome, these two genes were annotated as triphosphate tunnel metalloenzymes (TTMs) which were widely found in three superkingdoms of life with multiple substrate specificities and enzymatic activities, especially triphosphate hydrolase. In addition, the predicted structures of these two proteins were parallel, especially of the catalytic tunnel, including conserved domains, motifs, and folded structures. Their tertiary structures exhibited classic TTM properties, like the characteristic EXEXK motif and β-stranded anti-parallel tunnel capable of coordinating divalent cations. Moreover, MdTTM2 and HpAC1 displayed powerful hydrolase activity to triphosphate and restricted AC activity. All of these findings showed that MdTTMs had hydrolysis and AC activity, which could provide new solid evidence for AC distribution in woody plants as well as insights into the relationship between ACs and TTMs.